Pengembangan Media Pembelajaran Permainan Kartu Berbasis Make A Match Pada Mata Pelajaran Otomatisasi dan Tata Kelola Kepegawaian di SMKN 1 Jombang - Eka Aprilia Pravitasari; Durinda Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This development research resulted in a Card Game Learning Media Based on Make A Match in Automation and Governance Subject Class XI OTKP 1 Even Semester Academic Year 2018/2019. The purpose of this study was to determine: 1) the process of developing a media card learning game based on Make a Match; 2) the feasibility of a card game learning media based on Make a Match; 3) SMKN 1 Jombang students' responses to the media learning of card games based on Make a Match developed. This development refers to the 4D development model of Thiagarajan which has 4 stages namely define, design develop, and disseminate. Disseminate stage (dissemination) was not carried out because the research results were limited only to class XI OTKP 1 and focused on the material Functional Position and Structural Position in Competence Applying the Basic Rank of Departure (DUK) Employee Subjects in Automation and Staffing Governance. The instruments used in data collection and data analysis techniques used include media expert validation sheets and material expert validation sheets. In addition, data was also obtained from student response questionnaire sheets. This research was tested on 20 students of class XI OTKP 1 at SMKN 1 Jombang. The results of the study stated that the results of the validation of the learning media as a whole gained a score of 77.35% with a strong interpretation. Media expert validation was 75.2% and material expert validation was 79.5%. The results of student responses obtained a score of 80.2% with a strong interpretation. So it can be concluded that the learning media for card games based on Make a Match in the subject of Automation and Personnel Management in SMKN 1 Jombang is suitable for use in the learning process.